Reproduction and production of heifers implanted with Ralgro before weaning - D.D. Simms; F.L. Schwartz; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1982)
Over a 3-year period (1976-1978), heifer calves either were not implanted or were implanted between 2 and 5 months of age. In 1977, the study also included heifers implanted at birth. Implanting at birth increased the percentage of heifers open as yearlings. More implanted heifers tended to be open as 2- to 5-year-olds than control heifers, but the differences were not statistically significant. Implanting of the heifers had no effect on weight gains of their calves.
Keywords: Cattlemen' s Day; 1982; Report of progress (Kansas State University. Agricultural Experiment Station); 413; Beef; Implant; Weaning; Production